PENJATUHAN PIDANA DI BAWAH MINIMAL KHUSUS TERHADAP PELAKU TINDAK PIDANA ASUSILA DENGAN ANAK SEBAGAI KORBAN DI PENGADILAN NEGERI PURWOREJO - Sri Ari Astuti; Eko Nurharyanto (Universitas Janabadra, 2017)
This thesis discusses the issue criminal sentencing by a judge below the special minimum threshold under the Protective of Child Law in connection with the nulla poena sine lege principle. Based on the results of the research and discussion known that The decision of a judge in the Purworejo District Court who impose a criminal under-special imprisonment on the perpetrator of an immoral crime with a child as a victim is not appropriate if it is linked to the principle of legality in which it contains the element of legal certainty and expressly states that any criminal sanction shall be regulated in the law. While the basis of judges' consideration in imposing criminal under special minimum penalty is for the realization of justice for the defendant and for society. The imposition of a crime under a special minimum against a criminal offender against a child as a victim in the Purworejo District Court is based on the facts revealed in the trial and on the basis of justice principles. The factors that cause the judge to impose a criminal under special minimum penalty on the offender of immoral crime with the child as a victim are internal factors and external factors. These internal factors may include: the professional qualities of judges, judge intuitions and strong moral personality. The external factor is the guarantee of judicial freedom and independence of judges.